Impact of Learning Culture, Transformational Leadership and Motivation Language on Gen Y’s Employee Job Satisfaction: Case Study on a Islamic Banking - Ahmad Adriansyah; Bayu Wiranto (Indonesia Banking School, 2017)
One of the internal factors in the organization of Islamic Banks, or hereby BUS, considered important by regulators to be increased is their Human Resources, including in Bank X. Current human resources in the organization, including bank X, consisting of three generations, Generation Y, Generation X and Baby Boomer Generation. Each generation has different cognitive conditions, emotional states, and social conditions. This generation difference also affects the management of human resources in one company. This condition is the basis for doing human resources research on one generation only, namely Generation Y. Generation Y selection is because this generation will be the next generation in the company. One of the important factors related to human resources is its job satisfaction, which can determine the success of the organization, increase the productivity of employees and companies. Job satisfaction is caused by several factors, including those used in this study are Learning Culture, Transformational Leadership, and Motivating Language. The research was conducted at Bank X and attended by 216 employees who entered in Generation Y category. The test was conducted with SPSS 23, with Multiple Regression statistic methods. All measuring tools show good validity and reliability. The test results revealed that together the three factors above affect job satisfaction, with the proportion of influence of 47%. Transformational and Motivating Language Leadership variables significantly affect job satisfaction, while Learning Culture is not.